Desarrollo de la promoción turística en el distrito de Callahuanca, Provincia de Huarochirí-Lima desde la perspectiva de los visitantes, 2017 - Sanchez Quispe, Katherine Paola (2017)
The purpose of this research was to determine the development of tourism promotion at Callahuanca district. The research was realized with the contributions of Ortigoza and Gómez. The work area were all tourists who arrived at Callahuanca district, this research consists for 384 visitors to give the answers for a questionnaire of 28 items. The research was descriptive, no experimental and a cross sectorial in design. The collected data were processed by the SPSS statistical program 23 version. Finally, it was concluded tha the tourist promotion in Callahuanca district according to the 72 % of the interviewers is not adequate.